Validation of a noninvasive technique to quantify stress in northern bobwhite (Colinus virginianus) - Mohlman, Jessica L (Conserv Physiol, 2020)
Examination of the endocrine system through non-invasive fecal sampling may improve population management more than using demographic indicators alone. By addressing the physiological mechanisms that are influencing fitness, management actions can be proactively developed to alleviate stressors. Proactive determination of vulnerable populations is critical for species of concern, such as the Northern Bobwhite (Colinus virginianus), which have suffered decades of population decline. We validated an assay to noninvasively measure the adrenocortical response of captive reared bobwhite through fecal corticosterone metabolites (FCM). All individuals received three sequential 48-hour treatments in which samples were collected every 4 hours, including a reference period, an adrenocorticotropic hormone (ACTH) challenge and a biological stressor (exposure to a hunting dog). Reference FCM values had a mean concentration of 16.75 pg/mg (95% CrI: 13.68, 19.91) with adrenocortical activity increasing by 73% for the duration of the ACTH challenge (29.00 pg/mg; CrI: 25.01, 33.78). FCM concentrations remained similar to that of the reference levels during the biological stressor (16.56 pg/mg; CrI: 13.33, 19.92). Our study validates the use of feces to detect changes in FCM levels in our subject species but also demonstrates the complexity of FCM and the importance of both physiological and biological validation prior to field implementation.